Students’ Online Assessments in Higher Education Context: Indonesian Teacher Educators’ Voice - Didik Sucahyo; Desy Rusmawaty; Istanti Hermagustiana (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2022)
Background: The usage of remote learning system creates challenges in many universities, especially during COVID-19 pandemic. The utilization of remote learning system has supported many lecturers in teaching and learning process. However, making an appropriate learning assessment is still an issue. This study was aimed to investigate the types of assessment techniques, learning platforms utilized by lecturers in assessing the students’ performance, and challenges in assessing students online. Methodology: This is a mixed method study. The participants were 20 lecturers from any disciplines working in one state university in East Kalimantan, Indonesia. The data were quantitatively and qualitatively analyzed. Findings: It was revealed that six assessment techniques were revealed including video projects, group presentations, essay writing, online tests, summarizing, and giving comments on online discussions. Moreover, seven learning platforms were found to be used by the participants with Zoom as the highest choice with 86.2%. Last, three main challenges of assessing students online were uncovered through interview data which include lack of face-to-face interactions, lack of supporting teaching and learning facilities, and lack of students’ integrity and honesty. Conclusion: Various techniques and platforms for students’ assessments were used by lecturers. However, a number of challenges were also found to show that not only do online assessments provide positive but also negative contribution towards students’ performance in assessments.